The impact of entrepreneurial resilience on the success of small and medium enterprises in South Africa - Fatoki, Olawale (Sustainability, 2018)
Small and medium enterprises (SMEs) have a signiﬁcant role to play in a country’s sustainable development. The measures of a country’s sustainable development include economic and social factors. The sustainability of small and medium enterprises is vital to job creation, poverty reduction, and sustainable economic growth. The high failure rate of SMEs negatively impacts on South Africa’s sustainable development. The purpose of the study was to investigate the relationship between entrepreneurial resilience and the success of SMEs in South Africa. Success was measured using both organisational and individual criteria. The Connor–Davidson Resilience Scale 10 (CD-RISC 10) was used to measure entrepreneurial resilience. Data was collected from 170 small business owners through the survey method. The self-administered questionnaire method was used to collect data from the participants. Convenience and snowball methods were used for sampling. Descriptive statistics, conﬁrmatory factor analysis, correlation, and regression analysis were used for data analysis. Cronbach’s alpha was used as a measure of reliability. The results indicated that there is a signiﬁcant positive relationship between entrepreneurial resilience and individual and organisational success. Ways to enhance the resilience of small business owners in order to ensure the sustainability of SMEs are suggested.
European review of applied sociology
Keywords: Entrepreneurial resilience; Individual; Organisational; Success; Sustainability; Small and medium enterprises; South Africa; Small business--South Africa; Business enterprises--South Africa